2010
DOI: 10.1128/aac.00456-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Viability, Integrity, and Inflammation in Genital Epithelia upon Exposure to Pharmaceutical Excipients and Candidate Microbicides

Abstract: The use of microbicides is a promising approach for the prevention of HIV-1 transmission. Unfortunately, various candidates failed in clinical trials. In some cases, the candidate microbicide even resulted in enhanced virus transmission. Therefore, there is an urgent need to develop more predictive preclinical strategies to anticipate the in vivo efficiency/toxicity rate, including in vitro assays that evaluate effects on epithelial integrity and inflammation. The present study aims to identify potential safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…Furthermore, according to our own findings on the cytotoxic effects of gel formulations and excipients (i.e. constituents of gels such preservatives, co-solvents, surfactants and cyclodextrins) on female genital epithelium, the gel formulation used in this trial is non-cytotoxic under in vitro conditions [242]. These observations complement the trial findings on tolerability and safety of tenofovir gel.…”
Section: Reverse Transcriptase Inhibitorssupporting
confidence: 78%
“…Furthermore, according to our own findings on the cytotoxic effects of gel formulations and excipients (i.e. constituents of gels such preservatives, co-solvents, surfactants and cyclodextrins) on female genital epithelium, the gel formulation used in this trial is non-cytotoxic under in vitro conditions [242]. These observations complement the trial findings on tolerability and safety of tenofovir gel.…”
Section: Reverse Transcriptase Inhibitorssupporting
confidence: 78%
“…8,28,29 Although identified as generally-regarded-as-safe excipients by the Food and Drug Administration (FDA), several of these excipients were reported to affect the epithelial barrier in human cell culture or animal models. [18][19][20][21] Excipients chosen for evaluation represent a variety of functional categories and diverse chemical structures. The excipient concentration used in this study (Table 2) was determined based on the following considerations: Disodium EDTA is widely reported to decrease the integrity of intestinal cell monolayer (Caco-2) 30 and excised intestinal epithelium, 31 so three concentrations (0.05%, 0.1%, and 1%) were chosen to cover the relevant levels of use.…”
Section: Selection Of Excipients and Determination Of Experimental Comentioning
confidence: 99%
“…18 Several other tissue explant and mouse studies reported that treatment with excipients that are frequently used in vaginal products could alter the cervicovaginal tissue integrity and even increase the rate of vaginal herpes simplex virus 2 (HSV-2) transmission. [19][20][21] McClelland et al evaluated the effect of vaginal washing on the incidence of HIV-1 infection in 1,270 African women between 1993 and 2003. They found that women who partake in vaginal washing, by vaginal douching or washing with water and soap, had higher HIV acquisition risk as compared with women who did not perform vaginal washing.…”
mentioning
confidence: 99%
“…As a result, there is an urgent need to develop effective safe microbicides that can prevent HIV-1 infection. Damage to the vaginal epithelial surface due to certain chemicals and drug carriers can cause inflammation of the FGT (21,22), resulting in increased risk of HIV acquisition, as observed in several failed microbicide trials (23,24). Furthermore, the majority of microbicide studies have focused on the ability of the microbicide to induce inflammation in vaginal epithelial and immune cells (25).…”
Section: Discussionmentioning
confidence: 99%